Different modes of variation for each BG lineage suggest different functions. Issue 9 (September 2016) - Chattaway, John; Ramirez-Valdez, R. Andrei; Chappell, Paul E.; Caesar, Joseph J. E.; Lea, Susan M.; Kaufman, Jim
Abstract : Mammalian butyrophilins have various important functions, one for lipid binding but others as ligands for co-inhibition of αβ T cells or for stimulation of γδ T cells in the immune system. The chicken BG homologues are dimers, with extracellular immunoglobulin variable (V) domains joined by cysteines in the loop equivalent to complementarity-determining region 1 (CDR1). BG genes are found in three genomic locations: BG0 on chromosome 2, BG1 in the classical MHC (the BF-BL region) and many BG genes in the BG region just outside the MHC. Here, we show that BG0 is virtually monomorphic, suggesting housekeeping function(s) consonant with the ubiquitous tissue distribution. BG1 has allelic polymorphism but minimal sequence diversity, with the few polymorphic residues at the interface of the two V domains, suggesting that BG1 is recognized by receptors in a conserved fashion. Any phenotypic variation should be due to the intracellular region, with differential exon usage between alleles. BG genes in the BG region can generate diversity by exchange of sequence cassettes located in loops equivalent to CDR1 and CDR2, consonant with recognition of many ligands or antigens for immune defence. Unlike the mammalian butyrophilins, there are at least three modes by which BG genes evolve.